Inclusão pelo esporte: análise da motivação e da percepção dos participantes do projeto "a corda pra vida" - Ito, Iara Tocico (2017)
The sport beyond of physical condition sphere, can be an important education tool and social transformation, as presented in some articles. This work aims to analyze a social project with inclusion by sport, that use the sport as an educational tool associated with Token economy system, technique used by therapist. The objective was evaluate the motivation of participants to attend Rope Skipping (or Jump Rope) class, and evaluate if exist or not the perception of behavioral changes by participants and professionals involved in a project of social inclusion by sport. For this, the instrument IMPRAF – 54 was used and open questions directed to profissionals and athletes of this social project, in order to rise the perception about the technique used in classes. The most motivational dimensions were Pleasure, Competition and Health, result related to students answers in open questions. The results that showed the possibility of association the Token economy system with sport to seek positive social change.